Impact Velocity on Seashell Structure Reinforced Carbon Fiber Using Numerical Simulation - MatZin, Nadhirah; Kamarudin, Kamarul Azhar (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The purpose of this paper is to explore the seashells waste which can be used as the material for impact resistance in engineering applications. This research is conducted on a numerical simulation approach to predict the ballistic limit velocity for a hemispherical projectile that impacts the target plate. The simulation is conducted on two different target plates which are seashells with carbon fibre (seashells/CF) and fully seashells (without carbon fibre). The value of ballistic limit velocity and residual velocity due to the impact velocity for both analyses were compared. Based on the results obtained, the seashell structure target plate with carbon fibre reinforcement has a higher value of ballistic limit velocity compared to the seashell structure without carbon fibre reinforcement which is 11 m/s and 10 m/s respectively. The mechanical behaviour and impact damage of target plate were analysed based on the simulation conducted. It was observed that the performance of the seashells/CF target plate is better than the fully seashells target plate in terms of ballistic limit velocity, residual velocity, and impact damage.